2008
DOI: 10.1007/s00101-008-1439-2
|View full text |Cite
|
Sign up to set email alerts
|

Reanimation des Neugeborenen

Abstract: Although almost 10% of all newborn infants need some form of respiratory assistance after birth, only 1% will require more advanced forms of resuscitation. Because these rare events cannot always be anticipated, pediatricians and neonatologists may not be readily available and resuscitation will have to be performed by anesthesiologists. In recent years, international guidelines for neonatal resuscitation have been revised by the International Liaison Committee on Resuscitation (ILCOR), the American Academy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Despite the hyperosmolarity and carbon dioxide-generating properties of bicarbonate which might actually impair myocardial and cerebral function [18][19][20] , this belief permeated teaching of neonatal medical professional and clinical practice. Although present European guidelines for resuscitation at birth still allow the use of IVSB, recent updated guidelines from some countries do not even mention its use in the delivery room [10,11] . Moreover, updated reviews of the literature cast doubt on the usefulness of bicarbonate for acute correction of acidosis, and highlight the potential for IVSB to exacerbate myocardial and central nervous system damage [6,21,22] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the hyperosmolarity and carbon dioxide-generating properties of bicarbonate which might actually impair myocardial and cerebral function [18][19][20] , this belief permeated teaching of neonatal medical professional and clinical practice. Although present European guidelines for resuscitation at birth still allow the use of IVSB, recent updated guidelines from some countries do not even mention its use in the delivery room [10,11] . Moreover, updated reviews of the literature cast doubt on the usefulness of bicarbonate for acute correction of acidosis, and highlight the potential for IVSB to exacerbate myocardial and central nervous system damage [6,21,22] .…”
Section: Discussionmentioning
confidence: 99%
“…The International Liaison Committee on Resuscitation 2005 guidelines state that: 'Very rarely, a narcotic antagonist, sodium bicarbonate, or vasopressors may be useful during resuscitation' [8] . Coincidentally, national guidelines from the Netherlands, Germany and Canada do not even mention the use of IVSB during resuscitation [9][10][11] . However, in a recent study performed in our country (Spain), we showed that national/ international recommended resuscitation guidelines were only partially followed and that permeation of knowledge received during programmed cardiopulmonary resuscitation courses was not automatically put into practice [12] .…”
mentioning
confidence: 99%